A Propensity Score Cohort Study on the Long-Term Safety and Efficacy of Sleeve Gastrectomy in Patients Older Than Age 60. (1st August 2020) - Molero, Judith; Olbeyra, Romina; Vidal, Josep; Torres, Ferran; Cañizares, Silvia; Andreu, Alba; Ibarzabal, Ainitze; Jiménez, Amanda; de Hollanda, Ana; Moizé, Violeta; Flores, Lilliam
Abstract : Background . Bariatric surgery (BS) in older obese subjects (>60 years of age) has risen in the past decade and will continue to rise in the coming years due to ageing of the population. Aim . To evaluate the short- (12 months) and long-term (60 months) results of laparoscopic sleeve gastroscopy (LSG) in patients older than age 60. Methods . We performed a retrospective review of patients prospectively included in a database from January 2007 to December 2013. All patients >60 [older group (OG)] who had undergone LSG were included. The control group (CG) included patients aged 50 to 59 years who had undergone LSG during the same period. Results . 116 (8.4 % of total surgery) and 145 patients were included in the OG and CG, respectively. BS in patients >60 years increased from 2.4% in 2003 to 14% in the last 2 years of the study. After inverse probability of treatment weighting (IPTW) analysis, all absolute standardized differences were <0.15. A 60-month follow-up was attained in 90% of patients in the OG and 74% in the CG. There were no significant differences in postoperative complications between the two groups. At 12 and 60 months after LSG, both groups achieved a similar body mass index. There was no statistical difference in the percentage of resolution of type 2 diabetes, hypertension, dyslipidemia, and SAHS between the two groups. In both groups, all the nutritional parameters evaluated remained within the normal range throughout the study. Conclusions . LSG provides acceptable outcomes and is safe in older adults indicating that age should not be a limitation to perform BS in this population.